Different Tissue-Derived Stem Cells: A Comparison of Neural Differentiation Capability. - Gabriele Bonaventura; Sandrine Chamayou; Annalisa Liprino; Antonino Guglielmino; Michele Fichera; Massimo Caruso; Maria Luisa Barcellona (PLoS ONE, 2015)
Stem cells are capable of self-renewal and differentiation into a wide range of cell types with multiple clinical and therapeutic applications. Stem cells are providing hope for many diseases that currently lack effective therapeutic methods, including strokes, Huntington's disease, Alzheimer's and Parkinson's disease. However, the paucity of suitable cell types for cell replacement therapy in patients suffering from neurological disorders has hampered the development of this promising therapeutic approach.The innovative aspect of this study has been to evaluate the neural differentiation capability of different tissue-derived stem cells coming from different tissue sources such as bone marrow, umbilical cord blood, human endometrium and amniotic fluid, cultured under the same supplemented media neuro-transcription factor conditions, testing the expression of neural markers such as GFAP, Nestin and Neurofilaments using the immunofluorescence staining assay and some typical clusters of differentiation such as CD34, CD90, CD105 and CD133 by using the cytofluorimetric test assay.Amniotic fluid derived stem cells showed a more primitive phenotype compared to the differentiating potential demonstrated by the other stem cell sources, representing a realistic possibility in the field of regenerative cell therapy suitable for neurodegenerative diseases.